Hak Menguasai Negara Atas Sumber Daya Agraria - Julius Sembiring (BHUMI: Jurnal Agraria dan Pertanahan, 2016)
Abstract: State’s possession of agrarian resources , called as State’s right of control is the authority of the State attained through the atribution principle of the 1945 Constitution. In the National Land Law, the State’s right of control is the delegation of the public’s right to the State to manage resources, and was called as the highest right of the nation. Based on this delegation, the State has the authority to formulate policies, execute regulations, and also to arrange, manage, and control agrarian resources. To avoid misconducts on the implementation of the State’s right of control, the State authorities are limited by 3 (three) aspects, which are: the objective of the right itself for the greatest prosperity of the people; individual right and legal entity; and ulayat right of land of traditional society. On the implementation, State’s right of control was delegated to particular authorities (agrarian/land, forestry, and mining agencies), in which these authorities issuing civil rights such as ‘land right’ and ‘land permit’. K K K K Keywor eywor eywor eywor eywords ds ds ds ds: state’s right of control, agrarian resources, delegation of authority.Intisari: Penguasaan negara atas sumber daya agraria (SDA) yang disebut dengan hak menguasai negara (HMN) merupakan wewenang yang diperoleh negara berdasarkan prinsip atribusi dari UUD 1945. Dalam konsepsi Hukum Tanah Nasional, HMN tersebut merupakan pelimpahan hak publik berupa amanat untuk mengelola dari Hak Bangsa – sebagai hak yang tertinggi – kepada negara. Atas dasar pelimpahan tersebut, negara berwewenang untuk merumuskan kebijakan, melakukan pengaturan, pengurusan, pengelolaan dan pengawasan terhadap SDA.  Untuk menghindari kesewenang-wenangan dari HMN tersebut, maka kewenangan negara dibatasi oleh 3 (tiga) hal yaitu: oleh tujuan dari HMN itu sendiri yaitu untuk mencapai sebesar-besar kemakmuran rakyat; oleh hak perseorangan dan badan hukum; serta oleh hak ulayat masyarakat adat. Dalam pelaksanaannya HMN itu dilimpahkan pada otoritas tertentu (pertanahan, kehutanan, dan pertambangan) dan kemudian oleh otoritas tersebut diterbitkan hak yang berkarakter perdata seperti ‘hak atas tanah’ dan ‘izin’ kepada pihak tertentu. Kata kunci Kata kunci Kata kunci Kata kunci Kata kunci: hak menguasai negara, sumber daya agraria, pelimpahan wewenang